The place of the codification act in the legal system of Ukraine - Гетьман, Євген (Theory and practice of jurisprudence, 2017)
The analysis made it possible to conclude that the result of codification activity is fixed in the codification acts, which form the basis of legislation, code, statute, regulations, rules, instructions. The choice of the form of a codification act primarily depends on the authority that issued it. In connection with this, it should be emphasized that the provision of any codification act is more legal in relation to other normative legal acts, since, for example, the rules, approved by the Cabinet of Ministers of Ukraine, can not be in the hierarchical structure above, Than the code adopted by the Verkhovna Rada of Ukraine. When attributing this or that normative act to the codification, it is necessary to proceed not from the title of the document, but from the main features inherent in the codification acts as a whole.